TOWARDS THE USE OF HIGH STRENGTH STEEL AND CONCRETEIN HIGH-RISE CONSTRUCTION - Liew Jat Yuen, Richard (American Institute of Steel Construction, 2020)
Eighth International Conference on Composite Construction in Steel and Concrete